Efek Terapi Musik Klasik Terhadap Stabilitas Hemodinamik: Tinjauan Literatur Sistematis - Laloan, Risty Mandane (Yayasan Jompa Research and Development, 2025)
This systematic literature review explores the impact of classical music therapy on hemodynamic stability in clinical settings. As a non-pharmacological approach, classical music has shown promise in supporting cardiovascular regulation by promoting both physiological and psychological relaxation. This review synthesizes findings from 12 peer-reviewed studies published between 2020 and 2025, involving diverse patient populations including the elderly, ICU patients, surgical patients, and individuals undergoing hemodialysis. Results consistently show that listening to classical music—especially slow-tempo and soothing compositions—can significantly reduce blood pressure, heart rate, and respiratory rate. In addition, psychological benefits such as reduced anxiety and stress contribute to overall cardiovascular improvement. These outcomes are linked to activation of the parasympathetic nervous system and emotional regulation mechanisms. Despite variations in study design, music selection, and patient conditions, the collective evidence supports classical music therapy as an effective, low-cost, and non-invasive complementary treatment. The review emphasizes the importance of culturally appropriate music choices and standardized protocols to ensure consistent clinical outcomes. These findings offer practical insights for healthcare professionals aiming to integrate music therapy into routine care practices to enhance patient comfort, promote relaxation, and improve overall care quality.